If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14x + -67 = -11 Reorder the terms: -67 + -14x = -11 Solving -67 + -14x = -11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '67' to each side of the equation. -67 + 67 + -14x = -11 + 67 Combine like terms: -67 + 67 = 0 0 + -14x = -11 + 67 -14x = -11 + 67 Combine like terms: -11 + 67 = 56 -14x = 56 Divide each side by '-14'. x = -4 Simplifying x = -4
| p(-3)=3x^2-5x+7 | | P=4n+32 | | 5(x+1)+4(x+4)=75 | | -7+5=48 | | 4x+15+43=90 | | -0.5-2.7=-1.7 | | 6u+6-2(-4u-1)=2(u-3) | | -12x-10=-11x+16 | | Sin^4(3x/2) | | 6x^2y+8xy+2=0 | | 7(2b+1)-3b=29 | | 4a(a^4)7a=a(4a^3)+20 | | 6x^2y+8xy+2= | | 4x/4=29/8 | | 20/10=N/2 | | Sinx=0.234 | | -2x-6+-0.25x-3+90=180 | | 2138.9994=3.14r^2 | | -32c/(5*9) | | X11/4 | | T/5=-5/7 | | 2318.9994=3.14r^2 | | 3x-17*5=-66 | | 4x+5y=10.45 | | 2.27*34= | | 0.16(y-6)+0.10y=0.04y-0.3 | | 4(5+3x)=-52 | | 7(a+2)=-2(a-2) | | 3x+1y=3.85 | | 12n=162 | | (5a-3b)+(2a+6b)= | | x(x-6)=x^2+5x+4 |